School performance for children with cleft lip and palate: a population‐based study. (8th August 2016) - Bell, J. C.; Raynes‐Greenow, C.; Turner, R.; Bower, C.; Dodson, A.; Nicholls, W.; Nassar, N.
Abstract: Background: Educational attainment is important in shaping young people's life prospects. To investigate whether being born with orofacial cleft (OFC) affects school performance, we compared school test results between children born with and without OFC. Methods: Using record‐linked datasets, we conducted a population‐based cohort study of children liveborn in Western Australia 1980–2010 with a diagnosis of OFC on the Register of Developmental Anomalies, and a random sample of 6603 children born without OFC. We compared odds ratios for meeting national minimum standards in five domains (reading, numeracy, writing, spelling, grammar and punctuation), and adjusted OR (aOR) for children with cleft lip only (CLO), cleft lip and palate (CL + P) and cleft palate only (CPO) for each domain. Results: Results from two testing programs (WALNA and NAPLAN) were available for 3238 (89%) children expected to participate. Most met the national minimum standards. Compared with children without OFC, children with CPO were less likely to meet minimum standards for NAPLAN reading (aOR 0.57 [95%CI 0.34, 0.96]) grammar and punctuation (aOR 0.49 [95%CI 0.32, 0.76]), WALNA writing (aOR 0.66 [95%CI 0.47, 0.92]), and WALNA and NAPLAN numeracy (aOR 0.64 [95%CI 0.43, 0.95] and aOR 0.47 [95%CI 0.28, 0.82]), respectively. Children with CL + P had significantly lower odds for reaching the spelling standard in NAPLAN tests (aOR 0.52 [95%CI 0.29, 0.94]). Children with CLO had similar odds for reaching all minimum standards. Conclusion: Children born with OFC, particularly children with CPO, should be monitored to identify learning difficulties early, to enable intervention to maximize school attainment.